Effect of biomimetic templates on the magneto-structural properties of Fe3O4 nanoparticles. Issue 18 (5th March 2015) - Bhattacharya, Soumya; Roychowdhury, Anirban; Tiwari, Vivek; Prasad, Amresh; Ningthoujam, R. S.; Patel, Anant B.; Das, Dipankar; Nayar, Suprabha
<x xml:space="preserve">Abstract</x> The role of different biological templates in determining the morphology and properties of SPIONs.